THE CONCEPT OF NATIONALISM IN SRI AUROBINDO: A SPIRITUAL PERSPECTIVE ON POLITICAL IDEALS - Deshmukh, Pooja; Fatnani, Kinjal; Bhatt, Pina (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Indian patriotism has its origins in the ancient concept of Bharat Mata (Mother India), where the nation is seen as sacred. The freedom struggle against British rule (1857-1947) was the most significant expression of Indian patriotism, bringing together leaders, revolutionaries, and common people in a collective effort for independence. This research paper aims to delve into the nuanced and spiritual dimensions of nationalism as articulated by Sri Aurobindo, a visionary philosopher, yogi, and political activist during the early 20th century in India. While nationalism is often associated with political and socio-economic ideologies, Aurobindo's conception adds a unique spiritual layer to the discourse, emphasizing the integral development of both the individual and the nation. This paper explores the key aspects of Sri Aurobindo's nationalism, examining his views on political freedom, cultural identity, and the transformative role of spirituality in the pursuit of a higher collective consciousness.